2019
DOI: 10.1371/journal.pone.0218830
|View full text |Cite
|
Sign up to set email alerts
|

The plant-based by-product diets for the mass-rearing of Acheta domesticus and Gryllus bimaculatus

Abstract: Edible insect rearing could provide one alternative for protein production by having a smaller environmental impact than traditional livestock farming due to insects’ ability to convert organic side streams. Currently, the insect rearing industry utilizes soybeans as a major source of protein in the feeds. Protein-rich by-products of food industry could be used to replace them in insect feeds, but it is not known if they also meet the insects’ nutritional requirements. Our study evaluated the growth performanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(44 citation statements)
references
References 25 publications
7
31
0
Order By: Relevance
“…In this study, the survival of A. domesticus larvae was influenced by the diet. The survival rate was similar to the findings of Sorjonen et al [51] for insects reared on alternative diets at the age of 15-45 days, and similarly, low-protein alternative diets resulted in higher mortality. Contrary to our findings, Collavo et al [42] recorded an almost linear decrease in survival with time at the age of 1-81 days, with a survival rate of 47.5% on human refuse waste, as an example.…”
Section: Mass Of Live Larvae During Rearingsupporting
confidence: 88%
“…In this study, the survival of A. domesticus larvae was influenced by the diet. The survival rate was similar to the findings of Sorjonen et al [51] for insects reared on alternative diets at the age of 15-45 days, and similarly, low-protein alternative diets resulted in higher mortality. Contrary to our findings, Collavo et al [42] recorded an almost linear decrease in survival with time at the age of 1-81 days, with a survival rate of 47.5% on human refuse waste, as an example.…”
Section: Mass Of Live Larvae During Rearingsupporting
confidence: 88%
“…While assessing 18 diets based on industry by-products (such as, potato protein, barley mash, leftover of turnip-rape and broad beans) for rearing of crickets such as A. domesticus and G. bimaculatus , Sorjonen et al [ 109 ] reported yields of A. domesticus as high as 4.10 g on barley mash and 5.12 g of G. bimaculatus on turnip rape. The average weights of female and male A. domesticus were 0.459 g and 0.342 g, respectively, whereas in the case of G. bimaculatus the corresponding weights were 0.912 and 0.626 g. Thus, these protein-rich products can replace currently-used soybean in mass rearing.…”
Section: Nutrient Contentsmentioning
confidence: 99%
“…The increasing use of insects as food ingredients, developed at the same time that progress has been achieved in the factory farming of edible insects such as yellow mealworm ( Tenebrio molitor ), cricket ( Acheta domesticus , Gryllus bimaculatus ), or black soldier fly ( Hermetia illucens ) [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 ]. However, besides their relevant nutritional properties, products derived from edible insects may also exhibit some potential chemical safety risks due to the persistence of heavy metals or hazardous organic pollutants in the ready-to-eat insects [ 16 , 17 , 18 , 19 , 20 , 21 , 22 ], and microbiological and parasitological risks associated to the possible occurrence in edible insects of bacteria or parasites potentially pathogenic for humans [ 23 , 24 , 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%